Quality of maternal and newborn care services in Uganda: a scoping review - Brian Turigye; Edgar Mugema Mulogo; Jonathan Kajjimu; Joseph Ngonzi (Journal of Medicine, Surgery, and Public Health, 2025)
Despite significant advancements over the past two decades, mothers and newborns continue to experience preventable deaths, even when they give birth at healthcare facilities both globally and in Uganda. Evidence indicates that the quality of facility-based care may be a major factor contributing to this issue. This review aimed to identify, map, and synthesize all published studies on the quality of maternal and newborn care in Uganda. Following the Arksey and O’Malley five-stage framework for scoping reviews, a search strategy was employed to retrieve articles published over 20 years, from 2004 to 2024, in PubMed, EMBASE, and Web of Science. Two independent reviewers screened the extracted articles, first by title and abstract, and subsequently by full text, utilizing Covidence. Data were mapped according to the World Health Organization (WHO) Quality of Maternal and Newborn Care (QMNC) framework. Of the 2482 studies identified, 36 were included in this review. The majority of the studies focused on human resources and infrastructure, with few addressing the experience of care. Overall, the standards of care were inadequate across the studies, with particularly poor conditions noted in lower-tier government health facilities. Despite the critical importance of quality care in reducing maternal and newborn mortality, levels have remained persistently low in Uganda over the past 20 years, especially in public facilities. There is an urgent need to rethink the health system approach and delib erately enhance the quality of care if Uganda is to meet the 2030 global targets.
Keywords: Maternal; Newborn; Quality; Scoping; Uganda